BABY BLUES SYNDROME AND LEVELS OF HOUSEHOLD HARMONY: ISLAMIC FAMILY LAW CONCEPT - Asmita, Sri; Fathimah, Ema; Syarudin, Ahmad Zazili (Hukum Islam, 2024)
The trauma experienced by women after childbirth often leads to baby blues syndrome, which shows that the shock after childbirth can affect the physical and psychological changes of a woman. This paper aims to examine and analyse the phenomenon of baby blues syndrome experienced by postpartum women, which can affect family harmony and resilience, especially in the concept of Islamic family law. The study in this paper is descriptive qualitative. The data is collected through a library research approach and through the process of reading and searching on the Google search engine with the keywords "baby blues syndrome". This paper shows that baby blues syndrome experienced by postpartum women can be present in the form of trauma and acts of violence both to themselves and to children and even affect household harmony, even in the concept of Islamic Family Law, it is important to remember that a loving, understanding, and supportive attitude towards wives who experience baby blues syndrome is part of the responsibility of husbands and families in carrying out their respective roles. This is evidence that mental readiness before having a child is needed by a wife. This study shows that the baby blues condition is the cause of the breakdown of a family so that a comprehensive study of the phenomenon of baby blues syndrome is needed, which is expected to minimise the occurrence of baby blues syndrome in the household, so that family resilience can be maintained.